METHODS OF TEACHING-LEARNING-EVALUATING IN HIGHER EDUCATION AND SKILLS TRAINING - MUȘATA BOCOȘ; DANIEL ANDRONACHE; DORIN IONUȚ STANCIU; BACIU OANA RALUCA (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. The present paper aims to address briefly the teaching-learningevaluating methods used in higher education and how these methods determine and support competences training and development. Thus, we present several methods, such as: teaching-learning methods: lecture, lecture with discussion, heuristic conversation, didactic exercise, problem-solving, brainstorming, computer assisted learning; for assessment: traditional assessment methods: oral, written and practical evaluation; alternative evaluation methods: the continuous and self-evaluation, the essay, the project, the portfolio. Finally we propose a graphical model in which we highlight the relations of permanent interaction between the three components of the educational process - teaching, learning and assessment.